2022
DOI: 10.1002/cbdv.202200235
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils of Three Balkan Abies Species: Chemical Profiles, Antimicrobial Activity and Toxicity toward Artemia salina and Drosophila melanogaster

Abstract: This study focused on the essential oils (EOs) isolated from needles with twigs of three indigenous Balkan Abies species (A. alba, A. × borisii‐regis and A. cephalonica) regarding their chemical composition, antimicrobial activity and toxicity toward crustaceans and insects. Even though distinct phytochemical profiles of dominant volatiles were revealed for each species, β‐pinene and α‐pinene represented the first two major volatiles in all three EOs. Antimicrobial activity of EOs has shown inhibitory effect a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 32 publications
5
18
0
Order By: Relevance
“…performed the brine shrimp toxicity assay using about 30 ml of sample on Petri dishes, while Enneb et al. employed 100 ml of testing solutions [29,30] . The present study indicated that the modification of the original conditions of the brine shrimp bioassay, with the application of an experimental design and statistical techniques aiming to reduce the amount of biological sample needed for the test, was satisfactory.…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…performed the brine shrimp toxicity assay using about 30 ml of sample on Petri dishes, while Enneb et al. employed 100 ml of testing solutions [29,30] . The present study indicated that the modification of the original conditions of the brine shrimp bioassay, with the application of an experimental design and statistical techniques aiming to reduce the amount of biological sample needed for the test, was satisfactory.…”
Section: Resultsmentioning
confidence: 52%
“…Recently, Mitić et al performed the brine shrimp toxicity assay using about 30 ml of sample on Petri dishes, while Enneb et al employed 100 ml of testing solutions. [29,30] The present study indicated that the modification of the original conditions of the brine shrimp bioassay, with the application of an experimental design and statistical techniques aiming to reduce the amount of biological sample needed for the test, was satisfactory. The improvements to the test herein described allowed us to overcome the disadvantages presented in the original method, reducing the number of crustaceans used, the time, and the amount of sample to test.…”
Section: Production Of Amphibian Extractsmentioning
confidence: 75%
See 2 more Smart Citations
“…Fast screening of the biological activities of EOs facilitates quick access to knowledge, setting guidelines for more in-depth analyses. For this purpose, an array of bioassays can be employed [13] using very reliable model organisms, such as the common fruit fly Drosophila melanogaster Meigen (Drosophilidae) [14][15][16][17][18] and the crustacean species brine shrimp Artemia salina L. (Artemiidae) [19][20][21]. Both are eukaryotic model organisms with short life cycles and are very affordable for laboratory husbandry, allowing the rapid acquisition of experimental results [13,22,23].…”
Section: Introductionmentioning
confidence: 99%